Application of multiple criteria decision methods to optimise learning scenarios - Kurilova, Julija; Kurilovas, Eugenijus (Lietuvos matematikos rinkinys, 2016)
In the paper, learning scenarios (units) quality evaluation and optimisation problems are analysed. Learning scenarios optimisation is referred here as its personalisation according to learners needs. In the paper, comparative analysis of two popular optimisation methods based on Fuzzy numbers theory and Analytic Hierarchy Process is performed, aiming to measure what method is the most suitable to evaluate the quality of personalised learning scenarios. Learning scenarios quality is referred here as its suitability to learners needs. Research results show that Fuzzy numbers theorybased methods are more suitable to evaluate the quality of personalised learning scenarios.
Keywords: learning scenarios; fuzzy numbers; Analytic Hierarchy Process; optimisation; multiple criteria decision analysis; expert evaluation; learning components